A rose of blood and binding - Legrand, Claire, 1986- (Legrand, Claire, 1986- Middlemist trilogy, 2026)
"The battered Middlemist can barely hold itself together. Olden monsters terrorize the land. The gods are awakening from their ancient slumber, but if the vengeful Kilraith destroys them, all will be lost. And it's up to the Ashbourne sisters-demigods, daughters of the goddess Kerezen-to stop him. But the sisters are spread thin. Gemma and Talan travel the world in a desperate search for the gods. In the capital, Farrin and Ryder shelter countless refugees amid roiling unrest. And Mara Ashbourne, bound to the Middlemist and longing for a home she can never return to, is just trying to survive. Every day is chaos as Mara battles invaders and fights to protect her fellow Roses. The presence of librarian Gareth Fontaine-assigned to aid the Roses' war efforts-doesn't help. Charming, brilliant, far too confident, and annoyingly reverent of the Roses-Mara most of all-he's a distraction Mara can't avoid or afford. Especially since she can see the shadows of Mhorghast brimming underneath his dazzling smile. Shadows of violence and shame that she knows all too well. Shadows that terrify her more than any monster. As Mara and Gareth search the Old Country for Kilraith's final three curse-anchors, a slow-burning passion born of sorrow and solace sparks between them, one that could finally bring Mara to the very home she longs for...or drive her toward the dark fate she secretly craves, and bring both worlds crashing down alongside her"-- Provided by publisher.